The Influence of SISKEUDES, Internal Control System on Village Fund Accountability in Danau Kerinci Barat District, Kerinci Regency, Jambi Province - Safira, Siska; Sam, Iskandar; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2025)
This research aims to determine the influence of the Village Financial System and Internal Control System on the accountability of village fund management in West Lake Kerinci District, Kerinci Regency, Jambi Province. This research involved all villages in West Lake Kerinci District, Kerinci Regency, Jambi Province, totalling 14 villages. This research has 2 independent variables, namely the Village Financial System and Internal Control System, and 1 dependent variable, namely Village Fund Management Accountability. The population and sample in this study were 16 villages with a total of 56 respondents. The data used were primary and secondary data. Data collection techniques through distributing questionnaires. The tests used are data quality tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of tests carried out on all data obtained from 14 villages in West Lake Kerinci District, it can be concluded that the Village Financial System and Internal Control System significantly influence the accountability of village fund management in West Lake Kerinci District, Kerinci Regency, Jambi Province.